2019
DOI: 10.3389/fnmol.2019.00014
|View full text |Cite
|
Sign up to set email alerts
|

27-Hydroxycholesterol Contributes to Lysosomal Membrane Permeabilization-Mediated Pyroptosis in Co-cultured SH-SY5Y Cells and C6 Cells

Abstract: Purpose : Emerging evidence suggests that 27-Hydroxycholesterol (27-OHC) causes neurodegenerative diseases through the induction of cytotoxicity and cholesterol metabolism disorder. The objective of this study is to determine the impacts of 27-OHC on lysosomal membrane permeabilization (LMP) and pyroptosis in neurons in the development of neural degenerative diseases. Methods : In this study, SH-SY5Y cells and C6 cells were co-cultured in vitro to inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 57 publications
2
31
0
Order By: Relevance
“…Activation of this enzyme participates in another form of cell damage, namely pyroptosis (Espinosa-Oliva et al 2019;Wang et al 2019). Since previous data showed the activation of this proinflammatory protease in neuronal cell type, including SH-SY5Y cells and neuroprotective potency of its inhibitors (Chen et al 2019;Knaryan et al 2014;Nath et al 1996;Zhao et al 2019a, b), it is highly probable that this mechanisms could be responsible for synergistic protective action of Nec-1 and curcumin against H 2 O 2 -evoked cell damage, observed in the present study.…”
Section: Discussionsupporting
confidence: 63%
“…Activation of this enzyme participates in another form of cell damage, namely pyroptosis (Espinosa-Oliva et al 2019;Wang et al 2019). Since previous data showed the activation of this proinflammatory protease in neuronal cell type, including SH-SY5Y cells and neuroprotective potency of its inhibitors (Chen et al 2019;Knaryan et al 2014;Nath et al 1996;Zhao et al 2019a, b), it is highly probable that this mechanisms could be responsible for synergistic protective action of Nec-1 and curcumin against H 2 O 2 -evoked cell damage, observed in the present study.…”
Section: Discussionsupporting
confidence: 63%
“…Saeed et al [34] and Crick et al [31] have demonstrated that the concentration of 7α-hydroxy-3-oxo-4cholestenoic acid was remarkably elevated in CSF both from patients with a dysfunctional BBB and neurodegenerative disease including AD and Parkinson's disease (PD), or amyotrophic lateral sclerosis (ALS), which may be likely to re ect increased brain accumulation of 27-hydroxycholesterol as a result of damaged BBB integrity and increased serum levels of 27-hydroxycholesterol in MCI patients. The key role of 27-hydroxycholesterol in AD pathogenesis has been strongly supported by our previous animal and cellar research, pointing to the involvement of 27-hydroxycholesterol in the pro-in ammatory molecule release [35], oxidative stress [36], lysosomal membrane permeabilization and pyroptosis [37], synaptic dysfunction [38] and Aβ production [39]. We thus discovered and validated serum 27-hydroxycholesterol and 7α-hydroxy-3-oxo-4-cholestenoic acid as diagnostic biomarkers in MCI.…”
Section: Discussionsupporting
confidence: 63%
“…Pyroptosis is a pattern of cell death, which is consistent with the release of proin ammatory cytokines such as IL-1β and IL-18 [44]. Pyroptosis is closely associated with neuronal loss [45]. Exposure to zinc may cause in ammasome-mediated pyroptosis in olfactory neurons [46]; and 27-hydroxycholesterol contributes to the pathogenesis of neuronal death by inducing pyroptosis [45].…”
Section: Discussionmentioning
confidence: 93%
“…Pyroptosis is closely associated with neuronal loss [45]. Exposure to zinc may cause in ammasome-mediated pyroptosis in olfactory neurons [46]; and 27-hydroxycholesterol contributes to the pathogenesis of neuronal death by inducing pyroptosis [45]. Valproic acid attenuated neuronal impairment that was due to ischemic/reperfusion injury by inhibiting pyroptosis [47].…”
Section: Discussionmentioning
confidence: 99%